IDENTIFICATION OF THE TEMPORAL RELATIONSHIP BETWEEN THERMAL FRONT INTENSITY AND SKIPJACK FISHERIES PRODUCTION LANDED AT PPN TERNATE - Pratama, Gilar Budi; Pramesti, Retta Farah; Lady Ayu Sri (Jurnal Perikanan Unram, 2025)
The convergence of two oceans in Indonesian waters results in complex oceanographic dynamics, including the formation of thermal fronts. Thermal front areas are rich in nutrients, making them valuable for predicting potential fishing grounds. This study aims to identify the relationship between thermal fronts and skipjack tuna fisheries production landed at PPN Ternate, in order to assess whether thermal front data can be used to predict skipjack tuna fishing grounds in the area. The data utilized consists of fisheries production records and sea surface temperature images obtained from the Terra MODIS satellite. The images were processed using the Single Image Edge Detection (SIED) algorithm to map thermal front areas and measure their intensity. The relationship between thermal front intensity and skipjack tuna production was analyzed using Pearson correlation. The results show that thermal front areas are dynamically distributed around PPN Ternate every month, with increased intensity observed in February-March, July-October, and December. However, Pearson correlation analysis indicates no significant relationship between thermal front intensity and skipjack tuna fisheries production.